Uncertainty and Forword Exchange Speculation - Feldstein, Martin S. (The Review of Economics and Statistics, 1968)
CONSIDERABLE attention has recently I been given to the theory of foreign exchange operations and its implications for government policy. Central to this is the analysis of forward exchange speculation.' Although the essence of speculative behavior is the balancing of uncertainty and expected gain, the analysis of uncertainty in the current theory of forward exchange speculation has generally been less rigorous than other parts of that theory. The purpose of this paper is to present a more explicit theory of the role of uncertainty in forward exchange speculation in the framework of von Neumann-Morgenstern expected utility maximization and to explore its implications for speculator behavior and government policy. Section I is a brief review of the contemporary analysis of foreign exchange speculation. Section II presents the expected utility maximization theory and derives a mean-variance framework for analyzing speculator behavior. The effects of changes in the mean and variance of anticipated gain is discussed in section III, with speculation assumed to occur only in terms of one currency. The theory is extended to multiple currency speculation in section IV. Some policy implications are discussed in section V. Finally, section VI provides a brief summary.